Canadian stroke best practice recommendations: Management of Spontaneous Intracerebral Hemorrhage, 7th Edition Update 2020. Issue 3 (April 2021) - Shoamanesh (Co-chair), Ashkan; Patrice Lindsay, M; Castellucci, Lana A; Cayley, Anne; Crowther, Mark; de Wit, Kerstin; English, Shane W; Hoosein, Sharon; Huynh, Thien; Kelly, Michael; O'Kelly, Cian J; Teitelbaum, Jeanne; et al.
Spontaneous intracerebral hemorrhage is a particularly devastating type of stroke with greater morbidity and mortality compared with ischemic stroke and can account for half or more of all deaths from stroke. The seventh update of the Canadian Stroke Best Practice Recommendations includes a new stand-alone module on intracerebral hemorrhage, with a focus on elements of care that are unique or affect persons disproportionately relative to ischemic stroke. Prior to this edition, intracerebral hemorrhage was included in the Acute Stroke Management module and was limited to its management during the first 12 h. With the growing evidence on intracerebral hemorrhage, a separate module focused on this topic across the care continuum was added. In addition to topics related to initial clinical management, neuroimaging, blood pressure management, and surgical management, new sections have been introduced addressing topics surrounding inpatient complications such as venous thromboembolism, seizure management, and increased intracranial pressure, rehabilitation as well as issues related to secondary management including lifestyle management, maintaining a normal blood pressure and antithrombotic therapy, are addressed. The Canadian Stroke Best Practice Recommendations ( CSBPR ) are intended to provide up-to-date evidence-based guidelines for the prevention and management of stroke and to promote optimal recovery and reintegration for people who have experienced stroke, including patients, families, and informal caregivers.